COMPARISON OF CURCUMINOIDS EXTRACTION FROM TURMERIC (CURCUMA LONGA L.) RHIZOME AND ITS JUICE MARC USING FACTORIAL DESIGN - Agustian Darfiansyah, Irfan
Turmeric marc as a waste of producing turmeric juice and other fresh turmeric based product until now has not been used very well. Based on results of analysis, the dried turmeric marc still contained ethanol-soluble compounds in high quantities including curcuminoids. The fractional factorial design on turmeric extraction process using 6 factors showed that ethanol strength and the different types of materials (rhizome and its marc) were significant factors affecting curcuminoids content of the extract, while rhizomes part (mother and finger), ratio turmeric-solvent, temperature and duration of extraction did not show any significant effect on the content of curcuminoids in the extract. The liquid-liquid extraction process was performed on turmeric and its marc extract after each through extraction process using 90% ethanol with ratio turmeric-solvent 1:10 (w/v) at room temperature for 60 minutes and then evaporated. The first liquidliquid extraction was carried out using n-hexane to obtain organic phase, aqueous phase and the orange precipitate. The aqueous phase was divided into two, partly to be processed liquid-liquid extraction using ethyl acetate and the rest using dichloromethane, whereas the orange precipitate was filtered. All ethyl acetate and dichloromethane fractions were evaporated, then each concentrate and the orange precipitate were dried using conventional oven at 60 °C for 24 hours. Curcuminoids content of all samples were analyzed using High Performance Liquid Chromatography (HPLC). The result of factorial design analysis showed that the significant factor influencing the content of curcuminoids in the liquid-liquid extraction process was the different type of material (rhizome and its marc) while the different type of liquid-liquid extraction solvent (ethyl acetate and dichloromethane) showed no significant effect to the content of curcuminoids in the extract. However, the highest content of curcuminoids were not present in dichloromethane or ethyl acetate fractions, but on the orange precipitate obtained after liquid-liquid extraction using n-hexane. The following are the average of the curcuminoids content in the samples sorted from the highest to the lowest: orange precipitate from turmeric marc extract (PTME; 95.08%), orange precipitate from turmeric rhizome extract (PTRE; 70.37%), dichloromethane fraction of turmeric marc extract (DTME; 49.21%), ethyl acetate fraction of turmeric marc extract (ETME; 48.79%), dichloromethane fraction of turmeric rhizome extract (DTRE; 42.76%), ethyl acetate fraction of turmeric rhizome extract (ETRE; 40.34%), turmeric marc ethanolic extract (TME; 38.30%), and turmeric rhizome ethanolic extract (TRE; 29.59%). This study shows that the marc of turmeric rhizome from producing turmeric juice can be utilized in the manufacturing of curcuminoids with high content.